Comparison of management algorithms for the evaluation of women with low-grade cytologic abnormalities - Teresa L. Wright; Xin Sun; John P. Koulos (1995)
To present our clinical experience using a repeat Papanicolaou smear and human papillomavirus (HPV) DNA testing to evaluate patients with low-grade cytologic abnormalities. We performed a retrospective chart review of women who were referred for the evaluation of a Papanicolaou smear and were diagnosed as having either atypical cells of undetermined clinical significance or a low-grade squamous intraepithelial lesion (SIL). All women included in this review had a repeat Papanicolaou smear, HPV DNA testing with the Hybrid Capture method, and a colposcopic examination. The sensitivity and specificity of the repeat Papanicolaou smear for detecting biopsy-confirmed cervical intraepithelial neoplasia (CIN) were 0.74 and 0.67, respectively, in the 398 women referred for a previous low-grade SIL or atypical Papanicolaou smear. The sensitivity and specificity of a HPV DNA test positive for “high oncogenic risk” HPV types were 0.73 and 0.66, respectively. Triage using a repeat Papanicolaou smear and an HPV DNA test in combination correctly identified 92% of the women with biopsy-proven CIN, but 71% of the women would have been referred for colposcopy with this form of triage. A repeat Papanicolaou smear combined with a HPV DNA test is a sensitive alternative to colposcopic evaluation for the detection of CIN in women referred for a previous low-grade abnormal Papanicolaou smear. However, because of the low specificity of this approach, it results in only modest cost reductions compared to the more standard triage of performing colposcopy at the first visit.